A study to evaluate the antidiabetic effect of Syzygium cumini Linn. seed extract in high fructose diet induced diabetes in Albino Rats - Vihan, Sandeep; Brashier, D. B. S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The objective of the study was to evaluate the antidiabetic effect of syzygium cumini linn. Seed extract in high fructose diet induced diabetes in albino rats. Methods: This study was conducted in two phases. In Phase I acute and chronic effects of three doses of Syzygium cumini Linn 200mg/kg, 400mg/kg and 800mg/kg was seen in euglycaemic rats. In Phase II, the above doses of Syzygium cumini Linn were seen in diabetes induced by high fructose diet was evaluated. 5 groups of 06 animals each. Group I was given normal saline orally. Group II, III and IV were given oral Syzygium extract in the dose of 200mg/kg, 400mg/kg and 800mg/Kg respectively. Group V was given glibenclamide suspension 10 mg/Kg orally. Blood glucose was measured before starting this phase (Day 0), at the end of fructose feeding (day 28) and weekly thereafter up to the end of the treatment period (i.e. on days 35,42,49,56). Results: In phase I of the study, Syzygium extract had no effect on the mean blood glucose levels when given in the doses of 200, 400 and 800 mg/kg, from 1-24 hours. After chronic administration to euglycemic rats for 4 weeks, Syzygium extract also did not produce any significant change in blood glucose levels when given at various doses from 200-800 mg/kg. Treatment with all the three doses of Syzygium cumini extract (200,400 and 800mg/kg) produced a significant reduction in the blood glucose level. (P value <0.001 as compared to group I). The glucose lowering effect started at the end of 1 weeks and it increased till the end of the study in all the groups. Conclusions: Syzygium cumini Linn extract has no effect on the blood glucose levels of euglycemic animals. Syzygium cumini Linn extract can reduce blood glucose levels in high fructose diet induced diabetic rats, in a dose dependent and time dependent manner.